Efficiency and Equity Implications of Oil Windfalls in Brazil - Jorgensen, Ole Hagen (World Bank, Washington, DC, 2013)
Large oil reserves off the coast of Brazil may substantially increase the country s oil revenue in the future. A natural resource "curse" could be the consequence if an appropriate share of the oil revenue is not invested. This issue is addressed in this paper for Brazil both theoretically and empirically by focusing on (i) the efficient allocation of oil revenue between investment and consumption; and (ii) because it may be efficient to consume a certain share of the oil revenue, the distributional implications across generations of higher public consumption. The main finding is that, if the Pre-Salt oil revenue brings the aggregate oil revenue in Brazil above 10 percent of gross domestic product, there will be scope for consuming a certain share of it while still maintaining efficiency. But unless oil revenue reaches 10 percent or more of gross domestic product, then all of it should be invested in order for the economy to approach the efficient investment level. If oil revenue as a share of gross domestic product was 10 percent, then the achievable growth in gross domestic product could reach 9.0 percent. The distributional implications are positive for all generations, but vary across generations depending on how much of the oil revenue is invested. As a result, transfer policies could be adjusted to ensure equality in its distribution.